Comparative Transient Air-Flow Analysis for Integral Coach Factory (ICF) and Linke Hofmann Busch (LHB) Railway Coaches - deshmukh, sarthak; nikam, ronak; waghmare, sanskar; kondekar, yash; powar, sudesh (Journal of Railway Transportation and Technology, 2024)
Air-conditioning is a critical passenger comfort amenity on the Air-conditioned Indian Railways coaches. According to the data available, the Comfort Range (tolerance), and Comfort Zone (for FTA) are 23±1°C, ±5% RH, 23°C to 25°C all the time, anywhere and everywhere. The standard LHB (Linke Hofmann Busch) and ICF (Integral Coach Factory) - 2A coaches’ compartments of the Indian Railways are taken into consideration for the simulations and heat load calculations are performed on the complete coach. The inside temperature of the coach was determined to be between 300 K and 303 K for LHB and ICF coaches respectively and the time required for the inlet air (294-296K) to reach the thermal comfort temperature (298K) of 25°C was recognized. It was found that the time taken to reach the comfort temperature in an ICF and LHB coach is 310 sec and 163 sec respectively. From heat load calculations it can be stated that the ICF coach has a TR of 7.4217 Tons while the LHB coach has 8.2 Tons.